Show business homicides : an encyclopedia, 1908-2009 - Frasier, David K.; McDonough, Jimmy (Jefferson, N.C. : McFarland & Company, Inc., Publishers, 2011)
"A companion volume to the author's Suicide in the Entertainment Industry: An Encyclopedia of 840 Twentieth Century Cases (2002), this reference work chronicles 298 cases defined as "celebrity" homicides from the early twentieth century onward. Each entry covers the crime, its legal disposition, and the subject's personal and professional background, comprehensively documented with notes and a separate bibliography"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Performing arts -- Biography -- Dictionaries; Celebrities -- Biography -- Dictionaries; Entertainers -- Biography -- Dictionaries; Murder victims -- Biography -- Dictionaries